Good work if you can get it : how to succeed in academia - Brennan, Jason, 1979- (Johns Hopkins University Press, 2020)
"This is a short, punchy book about the real professional life of an academic. It provides hard data on what academic jobs are like and who gets them; on how to succeed in graduate school; on how to find time to write, teach, and have a personal life; and on what a person might do if academia does not work out. Written by a successful professor, the book warns aspiring academics about the harsh realities of an oversupplied job market and prepares them for playing by the rules that govern success in the academic profession"--